2016
DOI: 10.1016/j.enconman.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fuel-borne oxygen on European Stationary Cycle: Diesel engine performance and emissions with a special emphasis on particulate and NO emissions

Abstract: Exploration of sustainable fuels and their influence on reductions in diesel emissions are nowadays a challenge for the engine and fuel researchers. This study investigates the role of fuel-borne oxygen on engine performance and exhaust emissions with a special emphasis on diesel particulate and nitric oxide (NO) emissions. A number of oxygenated-blends were prepared with waste cooking biodiesel as a base oxygenated fuel. Triacetin, a derivative from transesterified biodiesel was chosen for its high oxygen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…As expected, the PN is inversely proportional to NO x emission. The outcomes achieved are consistent with previous issues announced in [32,75]. Nabi et al [75] found that the PN was oppositely relative to NO, with a very high correlation coefficient.…”
Section: Gaseous Emission Characteristicssupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, the PN is inversely proportional to NO x emission. The outcomes achieved are consistent with previous issues announced in [32,75]. Nabi et al [75] found that the PN was oppositely relative to NO, with a very high correlation coefficient.…”
Section: Gaseous Emission Characteristicssupporting
confidence: 80%
“…The outcomes achieved are consistent with previous issues announced in [32,75]. Nabi et al [75] found that the PN was oppositely relative to NO, with a very high correlation coefficient. Hydrous ethanol blends showed the lowest PN concentration and the lowest NO x than those of the anhydrous ethanol blend and gasoline.…”
Section: Gaseous Emission Characteristicssupporting
confidence: 80%
“…Another reason for higher NOx emissions with both DOP blends is the presence of fuel oxygen in their molecules. This excess oxygen can contribute to higher NOx emissions with the DOP blends [29]. CO is a useful marker for in-cylinder combustion quality.…”
Section: Exhaust Emissionsmentioning
confidence: 99%
“…Fuel oxygen content has been introduced as an influential factor in engine performance and emissions [20][21][22][23][24][25]. Song et al [23] investigated the effect of oxygen content on combustion in single-and multi-cylinder diesel engines using rapeseed biodiesel to vary the oxygen content of the diesel used.…”
Section: Introductionmentioning
confidence: 99%
“…This is seen in a further study by Zare et al [20], considering the performance and emissions of waste cooking biodiesel blends whose oxygen content was increased with the addition of triacetin. In previous studies with the same engine and fuels, engine performance and emissions (such as NOx and PM) has been reported during modal cycles [22], steady-state and transient operation [21,29] and cold start operation [30]. Compared to diesel with no oxygen content, when it comes to alternative fuels in the market, fuel oxygen content will be an important fuel properties which significantly affects the engine performance and emissions.…”
Section: Introductionmentioning
confidence: 99%